First Assessment of Mercury (Hg) Concentrations in Skin and Carapace of Flatback Turtles (Natator depressus) (Garman) From Western Australia - Schneider, Larissa; Tucker, Anton D.; Vincent, Kathryn; Fossette, Sabrina; Young, Erina J.; Whiting, Scott D. (Frontiers in Environmental Science, 2022)
Mercury (Hg) pollution in the surface ocean has more than doubled over the past century. Within oceanic food webs, sea turtles have life history characteristics that make them especially vulnerable to Hg accumulation. We investigated Hg concentrations in skin and carapace of nesting flatback turtles (Natator depressus) from two rookeries in Western Australia. A total of 50 skin samples and 52 carapace samples were collected at Thevenard Island, and 23 skin and 28 carapace samples at the Eighty Mile Beach. We tested the influence of size on Hg concentrations, hypothesising that larger turtles would exhibit higher concentrations due to more prolonged exposure to Hg. We compared the rookeries, hypothesising that the turtles from the southern rookery (Thevenard Island) were more likely to forage and reside in the Pilbara region closer to industrial mining activity and loading ports (potential exposure to higher environmental Hg concentrations) with turtles from the northern rookery (Eighty Mile Beach) and more likely to reside and feed in the remote Kimberley. Turtles from the Eighty Mile Beach rookery had significantly higher skin Hg concentrations (x̄= 19.4 ± 4.8 ng/g) than turtles from Thevenard Island (x̄= 15.2 ± 5.8 ng/g). There was no significant difference in carapace Hg concentrations in turtles between Eighty Mile Beach (x̄= 48.4 ± 21.8 ng/g) and Thevenard Island (x̄= 41.3 ± 16.5 ng/g). Turtle size did not explain Hg concentrations in skin samples from Eighty Mile Beach and Thevenard Island. turtle size explained 43.1% of Hg concentrations in the carapace of turtles from Eighty Mile Beach and 44.2% from Thevenard Island. Mercury concentrations in this species are low compared to other sea turtles, likely a result of the generally low Hg concentrations in the Australian environment. Although we predicted that mining activities would influence flatback turtle Hg bioaccumulations, our data did not support this effect. This may be a result of foraging ground overlap between sites, or the predominant wind direction carrying atmospheric Hg inland rather than seaward. This is the first Hg study in skin and carapace of flatback turtles and represents a baseline to compare Hg contamination in Australia’s surrounding oceans.